Transition metal complexes with 6, 7-dichloro-5, 8-quinolinedione as mitochondria-targeted anticancer agents. (1st May 2020) - Zou, Bi-Qun; Huang, Xiao-Ling; Qin, Qi-Pin; Wang, Zhen-Feng; Wu, Xue-Yu; Tan, Ming-Xiong; Liang, Hong
Graphical abstract: Complexes 1 and 2 arrested the cell cycle in the G1 phase, and inducing cancer cell death via mitochondrial dysfunction pathways was in the following order of 2 > 1 . Highlights: 5, 8-Quinolinedione transition metal complexes 1 –8 have been first reported. 1 –8 are more selective for HeLa cells versus normal cells (HL-7702). 2 also caused mitochondrial dysfunction. Abstract: Herein, a series of transition metal complexes, [Zn(DQ)2 (CH3 OH)2 ] (1 ), [Zn(DMQ)2 (CH3 OH)2 ] (2 ), [Co(DQ)2 (CH3 OH)2 ] (3 ), [Co(DMQ)2 (CH3 OH)2 ] (4 ), [Ni(DQ)2 (CH3 OH)2 ] (5 ), [Cu(DMQ)2 (CH3 OH)2 ] (6 ), [Mn(DQ)2 (H2 O)2 ] (7 ) and [Mn(DMQ)2 (H2 O)2 ] (8 ), containing 6, 7-dichloro-5, 8-quinolinedione (DQ) and 6, 7-dichloro-2-methyl-5, 8-quinolinedione (DMQ) ligands have been synthesized and characterized as potential antitumor agents. These complexes 1 –8 exhibited evident anti-tumor activity in HeLa (cervical), MCF-7 (breast), Hep-G2 (hepatoma), T-24 (bladder), and SK-OV-3 (ovarian) human cancer cells. Interestingly, complexes 1 –8 showed higher cytotoxicity than cisplatin against human cervical HeLa cells, and less cytotoxicity on the HL-7702 nontumorigenic cells. Mechanism studies suggested that complexes 1 and 2 arrested the cell cycle in the G1 phase and induced cancer cell death through mitochondrial dysfunction pathways. The cytotoxicity of 2 was higher than that of 1 . The different biological behavior of 1 and 2 may correlate with the presence of a 2-methyl group in 6, 7-dichloro-2-methyl-5, 8-quinolinedione (DMQ) ligand. In general, our study demonstrated that Zn(II) complex 2 with 6, 7-dichloro- 2-methyl-5, 8-quinolinedione showed high potential to be developed as a mitochondria-targeted metal antitumor agent.